Quality function deployment (QFD) reveals appropriate quality of charcoal used in barbecues - Ananias Francisco Dias Júnior; Carlos Rogério Andrade; Marcos Milan; José Otávio Brito; Azarias Machado de Andrade; Natália Dias de Souza (Scientia Agricola, 2020)
ABSTRACT: Charcoal is an important product widely used in food preparation in many parts of the world, both in developing and developed countries. However, most of the time, the main qualitative characteristics for consumers and the environment are not considered during production. Developing energy-efficient products for food preparation has been a constant pursuit of the charcoal supply chain and the aim of this study was to interact with charcoal consumers to become conversant with and classify the characteristics suitable for barbecue use. To achieve our objectives, we used the quality function deployment (QFD) method. The qualitative needs were deployed together with a multidisciplinary team assembled through interviews with several charcoal consumers. The cause and effect factors were also determined by the Ishikawa method. The technical demands of the product had the following priority order: ease of ignition, rapid formation of embers and flames, fast preparation of grilled food, and affordability. The factors relating to raw material, labor, and methodology emerged as decisive in the quality of charcoal for barbecue, and future studies should consider incorporating the results obtained in the production of charcoal and the respective consumer analysis.